2021
DOI: 10.46799/jsa.v2i3.193
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Pelatihan Modal Psikologis terhadap Keterikatan Kerja Pegawai Resto Kopi X Salatiga

Abstract: Peningkatan kualitas tenaga kerja di masa pandemi COVID-19 dapat dikatakan sebagai suatu hal yang penting untuk dilakukan. Hal ini mengingat bahwa tenaga kerja yang unggul adalah suatu kebutuhan utama bagi para pengusaha di masa post-pandemic yang akan datang. Berdasarkan asesmen awal yang dilakukan, ditemukan bahwa pegawai Resto X Salatiga membutuhkan sebuah intervensi yang bersifat psikologis untuk meningkatkan keterikatan kerja mereka. Berdasarkan kebutuhan tersebut, maka disusunlah penelitian eksperimen la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…Then in table 1.2, paired sample correlations show that 0.001 <, i.e., 0.001 < 0.05, meaning that there is a significant effect between the pre-test and post-test of psychological capital variables after being given HERO training. These findings are in line with the research of Wijaya (Wijaya, 2021), which also carries the concept of psychological capital training to increase work engagement. The training in research conducted by Wijaya (Wijaya, 2021) showed an increase in knowledge of the psychological capital of coffee restaurant employees after being given training.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Then in table 1.2, paired sample correlations show that 0.001 <, i.e., 0.001 < 0.05, meaning that there is a significant effect between the pre-test and post-test of psychological capital variables after being given HERO training. These findings are in line with the research of Wijaya (Wijaya, 2021), which also carries the concept of psychological capital training to increase work engagement. The training in research conducted by Wijaya (Wijaya, 2021) showed an increase in knowledge of the psychological capital of coffee restaurant employees after being given training.…”
Section: Resultssupporting
confidence: 90%
“…These findings are in line with the research of Wijaya (Wijaya, 2021), which also carries the concept of psychological capital training to increase work engagement. The training in research conducted by Wijaya (Wijaya, 2021) showed an increase in knowledge of the psychological capital of coffee restaurant employees after being given training.…”
Section: Resultssupporting
confidence: 90%